Standard practice for ultrasonic examination of turbine and generator steel rotor forgings. (American Society for Testing and Materials, 2009)
This practice for ultrasonic examination covers turbine and generator steel rotor forgings covered by Specifications A 469/A 469M, A 470/A 470M, A 768/A 768M, and A 940/ A 940M. This standard shall be used for contact testing only.